Photopatch testing in Chinese patients: A 5‐year experience. (5th March 2021) - Shao, Yixin; Hu, Yue; Wang, Duoqin; Zhu, Yiqi; Shen, Yanyun; Xu, Jinhua; Tang, Hui
Abstract: Background: In 2015, a Chinese expert consensus on photopatch testing (PPT) was established, based on European consensus methodology. Objectives: To update current information on the prevalence of photoallergic contact dermatitis (PACD) to 20 photoallergens and their clinical relevance in the Chinese context. Methods: A retrospective analysis of 2372 patients who performed PPT in a tertiary referral center in China between 2015 and 2019 was completed. A total of 1208 PACD reactions were observed in 897 (37.8%) patients, and 413 reactions were of current or past relevance. Results: The proportion of reactions of current or past relevance was 34.2%. The most frequent photoallergens were chlorpromazine, thimerosal, potassium dichromate, and formaldehyde. The ultraviolet absorbers, benzophenone and Para‐aminobenzoic acid, showed opposite gender distribution to PACD. Twenty‐five patients (1.9%) developed PACD reactions to a newly added photoallergen preparation – fragrance mix I. Patients with chronic actinic dermatitis, widespread exposed‐site or generalized dermatitis, and older age were more likely to have PACD. Conclusions: This study is the first to profile PACD reactions with clinical relevance in China. The prevalence of PACD to culprit photoallergens was affected by regional peculiarities. Attention needs to be paid to the age, body‐site distribution, and known diagnoses of patients for the identification of PACD.